2007
DOI: 10.1111/j.1540-8159.2007.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Nocturnal Heart Rate Variability and QT Dynamics in Patients with Brugada Syndrome

Abstract: Patients with a BSY-ECG pattern had lower HRV and QT/RR slopes than control subjects during nighttime. High-risk patients with spontaneous BSY-ECG patterns had the lowest nocturnal QTend/RR slopes. These unique repolarization dynamics might be related to the frequent nocturnal occurrence of VTA in BSY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
2
14
1
Order By: Relevance
“…It also has been shown that ST elevation increases after meals, especially dinner, in symptomatic patients 16 . The reports of bradycardia‐dependent episodes, the increased vagal tone in patients with VF, and the nocturnal predominance of the arrhythmic events support the hypothesis that the autonomic nervous system is involved in arrhythmogenesis 15–20 . The proposed mechanism is that bradycardia predisposes to increased current imbalance and extrasystoles, which may act at the vulnerable window for VT/VF.…”
Section: Discussionmentioning
confidence: 91%
“…It also has been shown that ST elevation increases after meals, especially dinner, in symptomatic patients 16 . The reports of bradycardia‐dependent episodes, the increased vagal tone in patients with VF, and the nocturnal predominance of the arrhythmic events support the hypothesis that the autonomic nervous system is involved in arrhythmogenesis 15–20 . The proposed mechanism is that bradycardia predisposes to increased current imbalance and extrasystoles, which may act at the vulnerable window for VT/VF.…”
Section: Discussionmentioning
confidence: 91%
“…Pierre et al [35] reported that 24-h ECG Holter of symptomatic Brugada patients were characterized by lower LF and HF components [6, 36], while other studies showed no differences in HRV between Brugada and healthy subjects, either during day or night [7]. When interpreting the contrasting results, several factors must be considered carefully: first, 24-h ECG Holter recordings do not differentiate between wake and sleep; second, comorbid (and often undiagnosed) SDB could potentially contribute to autonomic alterations; third, respiratory irregularities and apneas due to SDB would confound HRV measures; fourth, cardiovascular autonomic control is not stable during sleep, so it is essential to consider the different sleep stages.…”
Section: Discussionmentioning
confidence: 99%
“…55 In these patients SDNN 56 and LF power 57 of beating interval are reduced. A lack of sympathetic drive in the presence of sustained parasympathetic, drive together with a reduction in cAMP level (due to a direct feedback from a reduction in Na that decreases the Ca 2+ balance in the cell), were documented in patients with Brugada syndrome.…”
Section: Change In Hrv and Fractal-like Behavior In Cardiac Diseasesmentioning
confidence: 83%